Modeling of temperature dependence of Λ-graded InGaN solar cells for both strained and relaxed features - Sarollahi, Mirsaeid; Zamani-Alavijeh, Mohammad; Aldawsari, Manal A.; Allaparthi, Rohith; Maruf, Md Helal Uddin; Refaei, Malak; Alhelais, Reem; Mazur, Yuriy I.; Ware, Morgan E. (Frontiers in Materials, 2022)
Temperature dependence of -graded InGaN solar cells is studied through simulation using Nextnano software. -graded structures have been designed by increasing then decreasing the indium composition in epitaxial InGaN layers. Due to polarization doping, layers of p-type and n-type doping arise without the need for impurity doping. Different individual structures are designed by varying the indium alloy profile from GaN to maximum indium concentrations, x_max, ranging from 20% to 90% pseudomorphically strained to a GaN substrate and from 20% to 100% for completely strain relaxed material, then back to GaN again. For InxGa1-xN with x>~0.9, if the material is strained to the GaN lattice constant, it is predicted to have a negative bandgap. So, this case is not considered here. Temperature dependence of the electrical and optical properties as they relate to the solar efficiency of the -graded structures under relaxed and strained are studied. Additionally, the dimensionless absorption coefficients are fitted and plotted as functions of the bandgap for both strained and relaxed conditions at different temperatures. As a result, the generation rates as functions of the penetration depth within a cell can be calculated in order to obtain the solar cell parameters including efficiency for each -graded structure at different temperatures. For the strained condition, the x_max where the solar cell efficiency reaches its maximum for each temperature decreases as the temperature increases. At the same time, for the relaxed condition, at low temperatures (T=100 to 400 K) x_max is 100%, i.e., grading to InN results in maximum efficiency, while at higher temperatures (T=500 to 800 K), x_max decreases with increasing temperature.